How effective is weight loss in reducing cardiometabolic risk? An observational analysis of two randomised controlled trials of community weight loss programmes - Morris, E; Jebb, S; Oke, JL; Nickless, A; Ahern, A; Boyland, E; Caterson, ID; Halford, J; Hauner, H; Aveyard, P (Royal College of General Practitioners, 2020)
Background: Guidelines recommend clinicians identify individuals at high cardiometabolic risk and support weight loss in those with overweight or obesity. However, individual level data quantifying the benefits of weight change for individuals, to guide these discussions in primary care, is lacking.